LYMPHOGRANULOMATOSIS - Kurbankulov Uktam Muhammadovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Lymphogranulomatosis, also known as Hodgkin’s lymphoma, is a malignant disorder of the lymphatic system characterized by the proliferation of abnormal lymphocytes and the presence of Reed-Sternberg cells. The disease primarily affects lymph nodes and can spread to other organs if left untreated. Early diagnosis and accurate staging are essential for effective management and improved patient outcomes. This article reviews the epidemiology, etiology, clinical manifestations, diagnostic approaches, treatment strategies, and preventive considerations for lymphogranulomatosis, emphasizing the importance of timely intervention and multidisciplinary care.